Predictors of timeliness of vaccination among children of age 12-23 months in Boricha district, Sidama region Ethiopia, in 2019 - Berhan Tsegaye Negash; Yoseph Tediso; Amanuel Yoseph (BMC, 2023)
Abstract Background Traditional measurement of vaccine coverage can mask the magnitude of timely uptake of vaccine. Hence, the optimal measurement of timeliness is unclear due to variations in vaccine schedule among countries in the world. In Ethiopia, Oral Polio Virus (OPV), Pentavalent, Tetanus, H. influenza type B, Hepatitis B, and Pneumonia-Conjugate Vaccine (PCV) are basic vaccines which are taken at birth, six weeks, ten weeks, and fourteen weeks respectively. Despite its importance, information is scarce about on-time vaccination in the study area. Therefore, this study aimed to assess prevalence and factors associated with on-time vaccination among children of age 12-23 months in Boricha district, Sidama Ethiopia, in 2019. Methods A community based survey was conducted in Boricha district, Sidama region Ethiopia from January 1-30 in 2019. Study participants were selected using stratified multistage sampling technique. Kebeles were stratified based on residence. First, Kebeles were selected using random sampling. Then, systematic random sampling was employed to reach each household. Data were collected using structured and interviewer administered questionnaire. Logistic regression analysis was employed to identify factors associated with timely vaccination. Then, independent variables with p-value < 0.25 in COR were fitted further into multivariate logistic regression analysis model to control the possible cofounders. AOR with 95% CI and p-value < 0.05 was computed and reported as the level of statistical significance. Results From a total of 614 study participants, only 609 study participants have responded to questions completely making a response rate of 99.2%. Prevalence of timeliness of vaccination was 26.8% (95% CI: 25, 28) in this study. Factors like children of women with formal education (AOR = 5.3, 95%CI,2.7, 10.4), absence of antenatal care visit (AOR = 4.2,95%CI, 1.8,9.8), home delivery (AOR = 6.2,95%CI,4.0,9.3), lack of postnatal care (AOR = 3.7,95%CI,1.1,13.3), and lack of information about when vaccines completion date (AOR = 2.0, 95% CI,1.13,3.8) were factors influences timely vaccination among children of age 12-23 months. Conclusion Prevalence of on-time vaccination among children of age 12-23 months is lower than national threshold. Therefore, sustained health education on vaccination schedule and reminder strategies should be designed and implemented. Furthermore, maternal and child health care services should be enhanced and coordinated to improve on-time uptake of vaccine.